CLEAR CELL ODONTOGENIC CARCINOMA OF THE MANDIBLE WITH PERINEURAL INVASION: A REVIEW - Amin Rahpeyma; Saeedeh Khajehahmadı; Elahe Mahmoudi Hashemı (Cumhuriyet University, 2017)
Objectives: Clear cell odontogenic carcinoma (CCOC) is a rare aggressive cancer of the oral cavity. Diagnosis is mainly by excluding other pathologic lesions containing clear cells. Perineural invasion may be an important feature in this lesion. Methods: We performed a literature review. We paid attention to the CCOC and perineural invasion in the search of English language literatures in the Pubmed. Results: Analysis of previously reported cases of CCOC showed that up to2014 there were 74 reported CCOC cases in English articles, cited in PubMed. There was only one previous report of perineural invasion. Anew case is also presented in this article. Conclusion: Clear cell odontogenic carcinoma needs a special immunohistochemical protocol and complete workup to reach a correct diagnosis. Perineural invasion should be considered in central lesions of the mandible.